2022
DOI: 10.3390/children9121963
|View full text |Cite
|
Sign up to set email alerts
|

Parental Lifestyle Changes and Correlations with Children’s Dietary Changes during the First COVID-19 Lockdown in Greece: The COV-EAT Study

Abstract: The aim of this study was to investigate changes in the eating behaviour of parents during the first lockdown implemented in Greece due to COVID-19 and to explore possible associations with corresponding changes in the eating behaviour of their children. A quantitative cross-sectional study was performed using an online questionnaire. The study sample consisted of 397 parents with children aged 2–18 years, who were recruited from 63 municipalities in Greece. It was observed that the percentage of parents and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Rodríguez-Pérez et al [ 31 ] found a distinct trend in Spain; data showed that, during the lockdown, adherence to a Mediterranean Diet (i.e., olive oil, vegetables, fruit, low protein) [ 32 ] increased, and the intake of pastries and sweetened beverages decreased. Similar results were found in Greece, another European country following a Mediterranean Diet, where children decreased fast-food consumption and increased fruit and vegetables intake due to parents home-cooking more often during the lockdown [ 27 ].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Rodríguez-Pérez et al [ 31 ] found a distinct trend in Spain; data showed that, during the lockdown, adherence to a Mediterranean Diet (i.e., olive oil, vegetables, fruit, low protein) [ 32 ] increased, and the intake of pastries and sweetened beverages decreased. Similar results were found in Greece, another European country following a Mediterranean Diet, where children decreased fast-food consumption and increased fruit and vegetables intake due to parents home-cooking more often during the lockdown [ 27 ].…”
Section: Introductionsupporting
confidence: 75%
“…Staying at home also changed students’ eating habits. A study conducted in Greece suggested that children’s breakfast consumption during the first lockdown period increased in 5% [ 27 ]. In addition, there was a higher percentage of snack consumption (e.g., vegetables, dairy, sugary foods) overall, and a rise in food cravings during the lockdown compared to the period previous to the lockdown [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dates under study ranged from March 2018 (prepandemic reference) to April 2022 (during pandemic), although most studies collected data during January–December 2020. More information on characteristics of the studies can be found in Table 1 [ [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , ...…”
Section: Resultsmentioning
confidence: 99%
“… Self-reported Dietary recall Saltaouras et al. (2022) [ 89 ] 397 No info 2–18 y FFQ/questionnaire Breakfast, lunch, dinner, fast food Greece (0.89) March–May 2020 Compared with before lockdown, breakfast significantly increased. Fast food significantly decreased Parent-reported Dietary recall Schwarzová et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation